La motricidad fina y su influencia en la escritura en los estudiantes de la Escuela de Educación Básica Celeste Carlier Fuentes, del Cantón Quevedo 2022 - CALLE SANCHEZ LUIS GERARDO (2025)
The present study is developed at the “Celeste Carlier Fuentes” School of Basic Education in Quevedo for the period 2022, focusing on students at the Basic Elementary level as the field of study. The research approach is quantitative, the type of research is correlational, longitudinal and experimental, with a descriptive scope, among the theoretical methods applied were analysis-synthesis, documentary review, while the empirical methods correspond to the survey, interview, was applied to a non-probabilistic sample of 95 students, with an instrument validated by Cronbach's Alpha test that was equivalent to 0.708 reliable at a high level. The main results show a Pearson correlation of 0.803 with a p value of 0.02, a high correlation between the variables fine motor skills and writing, which is why it is necessary to have a program of activities to strengthen fine motor skills. Therefore, it must be applied in parallel to the planned pedagogical activities. It is concluded that students present difficulty in writing due to the lack of teaching support during the pandemic. Therefore, the author's hypothesis is affirmed that programmed fine motor activities would improve students' writing. Keywords: fine motor skills, writing, learning, reading, primary.